Bioavailable phosphorus across Florida’s diverse soil orders: implications for crop productivity and environmental protection - Nair, Vimala D.; Phuyal, Dinesh; Vardanyan, Lilit (Frontiers in Environmental Science, 2026)
Effective phosphorus (P) management is critical for sustainable agricultural production in Florida. The state’s diverse acid-mineral soils, including Alfisols, Entisols, Spodosols, and Ultisols, exhibit distinct physiochemical properties that profoundly influence P dynamics. This variability can lead to imbalanced P fertilizer applications, which can impair crop nutrient uptake and elevate the risk of environmental P loss. To address this challenge, a comprehensive statewide study of 1,711 surface soils (0–15 cm) was conducted across 14 regions in Florida. Our study evaluated the applicability of established agronomic thresholds for bioavailable P indicators, including the iron oxide strip method (FeO-P), the Haney test (H3A-P), and the conventional Mehlich-1 and Mehlich-3 extractions. Results revealed that the Mehlich 1-P and Mehlich 3-P relationship varied significantly by soil order; the Mehlich 3-P concentration corresponding to the 30 mg kg−1 Mehlich 1-P benchmark ranged from 41.8 mg kg−1 in Spodosols to 105.2 mg kg−1 in Ultisols. Mehlich-3 concentrations determined by ICP-OES were consistently higher than those measured using colorimetric methods, regardless of the soil order. The results confirm that a single, statewide agronomic Mehlich 3-P threshold is inadequate, as it could lead to overapplication in low P-fixing soils or deficiency in high P-fixing soils. Instead, P recommendations must be tailored to regional soil characteristics to ensure optimal crop productivity and minimize P loss to adjacent water bodies. Statewide bioavailable P thresholds are FeO-P = 21 mg kg−1 and H3A-P = 28 mg kg−1, both independent of the soil order. Integrating these thresholds with the Soil Phosphorus Storage Capacity framework provides a dual strategy to enhance crop nutrition while reducing environmental P loss.